Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients - Sauer, Christian; Römer, Alexandra; Späth, Monika; Kaden, Jens; Michel, Maurice Stephan; Mayer, Doris; Bleyl, Uwe; Grobholz, Rainer (Virchows Archiv, 2004)
Prostate cancer is the most common cancer in men and second in the cancer-related frequency of mortality. Matrix metalloproteinases (MMPs) are involved in tumor invasion and metastasis in various malignancies. MMP-2 and MMP-9 are capable of digesting collagen type IV. Numerous studies have demonstrated an association between increased MMP-2 and -9 expression and tumor progression in various tumors. In this study, the expression and activities of MMP-2 and -9 were assessed in serum probes and tumor tissue from core needle biopsies and radical prostatectomies of 97 patients. MMP-2 and -9 serum expression was analyzed in a subgroup of 31 patients. MMP-9 serum expression was significantly increased in tumor patients and correlated with tumor grade. In contrast, the MMP-9 tissue expression and activity revealed no significant correlations to tumor stage or grade. The MMP-2 activity, however, showed a positive correlation for MMP-2 with tumor stage. Increased activity was predominantly detected in advanced tumor stages. Immunohistochemical analysis of MMP-2 expression demonstrated a positive association with tumor grade in prostatectomy specimens. The relative expression rates in biopsies matched in 65% with those of the prostatectomies. Detection of MMP-2 in core needle biopsies seems not to be a helpful marker for diagnostic purposes.